Efektivitas Penggunaan Game Kahoot terhadap Hasil Belajar Siswa Mata Pelajaran PAI XI SMAN 1 Lembang Jaya - Wahyuni, Sofia Putri; Alfurqan, Alfurqan (Lembaga Yasin AlSys, 2023)
This research is motivated by the current learning atmosphere which has not been able to motivate students well, resulting in student learning outcomes that are not yet optimal. This is because the exercises in the learning process are still not varied enough, one example of training that can be used is Kahoot. This research aims to determine the effectiveness of using the Kahoot quiz game on the learning outcomes of class IX students at SMA Negeri 1 Lembang Jaya. This research uses a quantitative approach with the experimental method